Ethnic Cultural Tourism Resources Evaluation and Development: Kazakh Cultural Tourism Resources Analysis - SAIKEN, Adayi; ZHAOPING, Yang; MAZBAYEV, Ordenbek; DUISSEMBAYEV, Azamat; IZENBAEV, Beknur; NASSANBEKOVA, Samalgul (Journal of Environmental Management and Tourism, 2017)
Evaluation of tourism resources of national culture requires effective development of ethnic cultural tourism resources and identification of the development of the main body as well as provision of a scientific basis for decision-making. At the present, commonly used practice of tourism development methods in our country are qualitative evaluation and quantitative evaluation. In most cases, those methods are only applicable for the natural tourism resources, but that is not a perfect assessment method for ethnic cultural tourism resources. Based on the results of previous studies, this article attempts to use a new method on tourism resources evaluation of Kazakh ethnic cultural resources, whereby mainly adopts qualitative index and quantitative index from the fuzzy evaluation method. The method of qualitative evaluation is often based on the expert’s wealthy experience and knowledge, and their results are always partial to decision-making demand of the expert. Therefore, their evaluation results belong to the kind of subjective evaluation. Quantitative evaluation method is trying to make the resources assessment more objective and accurate, but the evaluation of the impact of the subjective factors is unavoidable. To reduce the influence of human factor for the evaluation, the result has to suit achievable measures, which adjust measures to local conditions on index extraction, method selection and model building and to make every effort to correspond to reality, to be objective, and to be accurate evaluation. A fuzzy comprehensive evaluation method is a kind of fuzzy reasoning based on the combination of qualitative and quantitative, exact and inexact unified evaluation method. This kind of method in cultural tourism resources evaluation has good theoretical guidance and practical operation.